Leaf-templated synthesis of hierarchical AgCl-Ag-ZnO composites with enhanced visible-light photocatalytic activity. (July 2018) - Cai, Aijun; Guo, Aiying; Du, Liqaing; Qi, Yanling; Wang, Xiuping
Graphical abstract: Highlights: Leaf-templated AgCl-Ag-ZnO composites were obtained. The catalysts exhibit excellent visible-light photoctalytic activity. Electrons and holes of catalyst are efficiently separated. Abstract: In this paper, poplar leaf is used as a template to synthesize hierarchical AgCl-Ag-ZnO composites via a calcination method. Zn(NO3 )2 and AgNO3 are selected as precursors. During the calcination of the templates, Zn 2+ ions react with oxygen to produce ZnO nanoparticles (NPs), Cl − ions in leaf cells combine with the external Ag + ions to form AgCl, and Ag + ions are reduced by reducing agents in leaf to Ag NPs. The morphology, structure and visible-light response of the as-prepared hierarchical AgCl-Ag-ZnO composites are determined. The composites exhibit a strong photocatalytic activity toward the degradation of Rhodamine B (RhB) under visible-light irradiation. The AgCl-Ag-ZnO composites display an enhanced photocatalytic activity, compared with the leaf-templated AgCl-Ag and ZnO. A photocatalytic mechanism is proposed, based on the efficient separation of photoexcited electron-hole pairs due to the surface plasmon resonance (SPR) effect of metal Ag.